Implikasi Hukum Adat terhadap Pembagian Warisan Anak Perempuan Perspektif Hukum Keluarga Islam - Liky Faizal; Efa Rodiah Nur; Abd. Qohar; Hilmi Yusron Rofi'i (Faculty of Law, Universitas Pekalongan, 2025)
Indigenous peoples of Lampung have a tribal culture which is divided into two large customary groups, namely the Saibatin and Pepadun indigenous peoples, and most of the community members embrace Islam, in terms of marital affairs which will continue to be inherited in the family. Indigenous people in general still use the procedures contained in their customary law. This study aims to analyze the position of women in inheritance distribution in Lampung customary law in Way Kanan and Pesisir Barat districts from the perspective of Islamic Family Law in Indonesia. This research is field research, which describes and describes the situation and phenomena more clearly regarding the situation that occurred. This study intensively studied the position of women in inheritance distribution in Lampung customary law in Way Kanan and Pesisir Barat districts from the perspective of Islamic Family Law in Indonesia. Qualitative descriptive research method is research that only describes situations and events. This study does not seek or explain relationships, does not test hypotheses or make predictions, but only describes variable by variable. This study uses a purposive sample. The informants in this study were: Key Informants: 4 traditional leaders, Main Informants: 4 women who were heirs, Supporting informants: 4 indigenous people. Data sourced from primary data and secondary data, with data collection techniques interview, observation, and documentation. The data collection activities are carried out after the research is carried out or compiled. Data collection is one of the processes in research that can help solve the problems being studied, therefore the data collected must be sufficient. Data analysis by collecting data, data reduction, data presentation, and conclusions.